Sosialisasi Stunting di Desa Jambai Makmur: Meningkatkan Kesadaran Masyarakat akan Gizi Anak - Adi Saputra Jaya Sitorus; Afifah Syafina Maghfirah; Geby Ella; Lasma Rohana Anessta Sitindaon; Nanci Nanci; Nurliani Nurliani; Renita Siringo-ringo; Sehat Hasiholan Hutaean; Widia Silvia Siahaan (LP2M Universitas Muhammadiyah Enrekang, 2023)
Stunting, a condition of growth failure in children under two years old due to chronic malnutrition, is a serious public health concern in Indonesia. This article reviews the development of stunting in Jambai Makmur, a village in Siak District. The impact of stunting is that it stunts a child's physical growth but also poses challenges to weak thinking skills and long-term health problems for affected children. The Real Work Lecture (KKN) program implemented in Jambai Makmur Village aims to overcome the problem of stunting through stunting socialization. This socialization aims to improve general understanding of the causes, impacts, and prevention measures of stunting, emphasizing community involvement and education. This article covers the procurement of permission from the Puskesmas of Jambai Makmur Village, preparation of materials, and snacks and the implementation of stunting socialization. As a result, the community responded to the socialization and increased community awareness, especially mothers, about stunting.